Modeling of Soft Sample Deformation in Atomic Force Microscope Imaging: Live Mammalian Cell Example. Issue 1 (16th October 2018) - Ren, Juan; Zou, Qingze
Abstract: A model of the scanning‐caused soft sample deformation during atomic force microscope contact‐mode (CM) imaging is developed. CM imaging has been widely used for topography characterization of live biological samples such as live cells. However, due to the intrinsic softness of these samples, the sample surface deformation caused by the probe–sample interaction leads to significant error in the topography images obtained, and damage to the live biological sample. Although the deformation can be reduced by imaging at a rather slow scan rate (e.g., less than 0.2 Hz), such a low‐speed imaging not only is time consuming, but also inevitably induces large temporal error. In this work, the scanning‐caused surface deformation of soft samples is modeled and quantified, including live biological samples in CM imaging. Effects of both the scanning and the coupling between the vertical and the lateral deformation on the deformation are characterized. The proposed deformation model is validated by implementing it to quantify the topography image difference caused by the scanning‐caused surface deformation of live prostate cancer cells imaged at two different (high and low) speeds, respectively. Abstract : A dynamics model of the scanning‐caused sample deformation during contact‐mode imaging in atomic force microscopy is proposed. Both the scanning‐ and the vertical‐to‐lateral‐coupling‐caused deformation are characterized. The proposed deformation model is validated through quantification of the difference of the topography images of live prostate cancer cells obtained at different scanning speeds.